Konsep Diri Perempuan Bali Melawan Patriarki dalam Novel Tempurung Karya Oka Rusmini - Barokah, Aas Nurasiah; Hermawati, Yessy (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Oka Rusmini is an Indonesian writer who is consistently write a story of women especially a Balinese women. The purpose of this study is describe how self concept displayed by Balines women fights patriachical power in Oka Rusmini by novel Tempurung. The Lacanian psychoanalytical approach is employed to point out pscyche factors undergone by Balinese women. Through desire showed by women characters in the novel Tempurung, it can by analysed how self concept is formed. The selft concept of the Balinese women that are displayed; physical self concept, social self concept, moral self concept, and psychological self concept.